2010
DOI: 10.1002/bjs.6870
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of randomized controlled trials on the safety and effectiveness of early versus delayed laparoscopic cholecystectomy for acute cholecystitis

Abstract: Conclusion: ELC during acute cholecystitis appears safe and shortens the total hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
152
4
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(170 citation statements)
references
References 58 publications
8
152
4
6
Order By: Relevance
“…The somewhat higher proportion of early laparoscopic procedures that had to be converted to an open procedure is predictable and reflects good clinical judgment. Studies from specialized centers show no major differences in complexity and conversion rates between EC versus DC [9,10,11,12,13,14,15,16]. In the present study, the conversion rate was higher than that reported from specialized centers (tables 2, 3).…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…The somewhat higher proportion of early laparoscopic procedures that had to be converted to an open procedure is predictable and reflects good clinical judgment. Studies from specialized centers show no major differences in complexity and conversion rates between EC versus DC [9,10,11,12,13,14,15,16]. In the present study, the conversion rate was higher than that reported from specialized centers (tables 2, 3).…”
Section: Discussioncontrasting
confidence: 66%
“…In a recent meta-analysis, Gurusamy et al [9] found that 17.5% of patients in the delayed group underwent emergency surgery during the waiting period due to gallstone-related problems. We observed a cumulative re-admission rate, 1 year after the index admission for AC, of 17.8% in patients treated conservatively and where the DC/DLC strategy was applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both meta-analyses found that there were no signifi cant differences in conversion rates to open procedures, incidence of common bile duct injuries, or postoperative complications. Early laparoscopic cholecystectomy is also associated with a shorter hospital length of stay and lower total hospital cost [ 63 ]. It should be noted that in one of the meta-analysis, the incidence of bile leaks was higher in the early cholecystectomy group (3 % vs. 0 %) [ 63 ].…”
Section: Treatment Of Acute Calculous Cholecystitismentioning
confidence: 96%
“…Early laparoscopic cholecystectomy is also associated with a shorter hospital length of stay and lower total hospital cost [ 63 ]. It should be noted that in one of the meta-analysis, the incidence of bile leaks was higher in the early cholecystectomy group (3 % vs. 0 %) [ 63 ]. Also, due to the small number of total patients in these pooled randomized trials (451), the incidence of common duct injury could easily be over or underrepresented in either group due to the low overall incidence of this complication (0.4-0.6 %) [ 65 ].…”
Section: Treatment Of Acute Calculous Cholecystitismentioning
confidence: 99%